1993
DOI: 10.1172/jci116206
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin stimulates proliferation of cultured rat aortic smooth muscle cells by a proteolytically activated receptor.

Abstract: Thrombin has been implicated in the stimulation of smooth muscle cell (SMC) proliferation that contributes to post angioplasty restenosis. The present studies demonstrated that human a-thrombin was a potent and efficacious mitogen for cultured rat aortic SMC, stimulating an increase in 3H-thymidine incorporation, as well as an increase in cell number at 1 to 10 nM concentration. -Thrombin, which is enzymatically active but lacks fibrinogen clotting activity, stimulated SMC mitogenesis but was -10-fold less pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
297
0
7

Year Published

1996
1996
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 506 publications
(318 citation statements)
references
References 35 publications
14
297
0
7
Order By: Relevance
“…Previous studies have shown that thrombin is a mitogen for many cell types, including vascular smooth muscle cells, 36,37 fibroblasts, 38,39 endothelial cells, 40 mesangial cells 41 and osteoblasts. 4 In many of these cells, proliferation is known to be mediated by PAR-1 and in osteoblasts, in particular, we have recently confirmed that proliferation is mediated by PAR-1.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that thrombin is a mitogen for many cell types, including vascular smooth muscle cells, 36,37 fibroblasts, 38,39 endothelial cells, 40 mesangial cells 41 and osteoblasts. 4 In many of these cells, proliferation is known to be mediated by PAR-1 and in osteoblasts, in particular, we have recently confirmed that proliferation is mediated by PAR-1.…”
Section: Discussionmentioning
confidence: 99%
“…1 Thrombin can also contribute to the development of graft neointimal hyperplasia through its action as a smooth muscle cell mitogen, a mediator of inflammation, and an agonist for the release of platelet-derived growth factor. [2][3][4][5] Hirudin, a 65-amino acid protein secreted by the salivary glands of the medicinal leech, is a potent and specific inhibitor of thrombin. 6 By blocking both the catalytic site and the anion-binding exosite of thrombin, hirudin inhibits the interaction of thrombin both with fibrinogen and with thrombin receptors that are present on the surface of platelets and vascular cells.…”
Section: Introductionmentioning
confidence: 99%
“…Thrombin generated at sites of vascular injury is the most potent activator of blood platelets [7,8] and its action on inflammatory cells has been well characterized, serving as a chemotactic agent for monocytes [9] and a mitogenic for both lymphocytes [10] and vascular smooth muscle cells [11,12]. Thrombin activation of the vascular endothelium occurring in response to vascular injury or wounding can be beneficial in the repair process, but has the potential to mediate a prolonged inflammatory response and proliferative cellular events in the blood vessel wall, such as those that occur in atherosclerosis and restenosis [13].…”
mentioning
confidence: 99%